Pengaruh Metode Seleksi Terhadap Kualitas Karyawan Baru - Warohmah Warohmah; Hendra Riofita (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
Effective selection methods are key to ensuring that the selected candidates not only meet the required qualifications, but also fit the company culture and values. Through the use of various tools and techniques such as interviews, aptitude tests, and psychological assessments,companies can improve the quality of employees they recruit. The research results show that systematic and rigorous selection methods contribute to improving employee performance, reducing turnover rates, and increasing team stability. In addition, ongoing evaluation of the selection process is also important to ensure its relevance and effectiveness. Thus, investing in appropriate selection methods will produce high-quality employees who can contribute positively to organizational goals. This research provides recommendations for companies to adopt a combination of various selection methods and carry out regular evaluations to improve recruitment results.